If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.5w + -16 = 8 Reorder the terms: -16 + 1.5w = 8 Solving -16 + 1.5w = 8 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 1.5w = 8 + 16 Combine like terms: -16 + 16 = 0 0 + 1.5w = 8 + 16 1.5w = 8 + 16 Combine like terms: 8 + 16 = 24 1.5w = 24 Divide each side by '1.5'. w = 16 Simplifying w = 16
| 7-8x=13x+11+x | | -1/6+z=-1/11 | | 1/6+z=-1/11 | | (9t+4)(5t-15)=0 | | (2x+4)=(3x+8) | | -135=-9n | | 5(3t-5)=6(2t+3) | | -1/3+2x=-5/6 | | 3/2x-19=18 | | m/-2=11 | | 81t^4-16u^4=0 | | 9x+14=3(3x+5) | | 6v^2-42v=0 | | 3a+7b=82 | | 3*42/6 | | -76=2(-8+5v) | | (x-4)/(x^2+2) | | 8x+8=7x+13 | | -3n-6=0 | | 4x-5+7=10 | | X=(4-1/3)/(1/3) | | -8r-8r=0 | | F=1/3(41)+1/3 | | F=1/3(12)+1/3 | | 4x-20=-6x | | (6k-7)(8k+5)= | | 3.333+y=6 | | 2x+37=5x+4 | | (2x-3)(2x-3)(2x-3)=0 | | 3x/-8=-3 | | 5=4x+8 | | 2f(5f-2)-10(f^2-3f+6)=-8f(f+4)+4(2f^2-7f) |